2008
DOI: 10.1128/jvi.01242-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of cdk9 in the Optimization of Expression of the Genes Regulated by ICP22 of Herpes Simplex Virus 1

Abstract: ICP22 is a multifunctional herpes simplex virus 1 (HSV-1) regulatory protein that regulates the accumulation of a subset of late (␥ 2 ) proteins exemplified by U L 38, U L 41, and U S 11. ICP22 binds the cyclin-dependent kinase 9 (cdk9) but not cdk7, and this complex in conjunction with viral protein kinases phosphorylates the carboxyl terminus of RNA polymerase II (Pol II) in vitro. The primary function of cdk9 and its partners, the cyclin T variants, is in the elongation of RNA transcripts, although function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 40 publications
(51 reference statements)
5
61
0
Order By: Relevance
“…Since CDK9/cyclin T1 complex was reported previously to be required for the replication of other viruses of Herpesviridae origin, we next verified the antiviral effect of FIT-039 on tion through phosphorylation of the CTD of RNA polymerase II and viral proteins, such as the ICP22 of HSV. The ICP22-CDK9 complex was reported previously to phosphorylate the CTD of RNA polymerase II and regulate the transcription of HSV (20,22). A previous study showed that CDK9 was localized to nuclear viral transcriptosomes at the immediate-early stage of the HCMV infection, which allowed the active transcription of HCMV IEGs (14).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since CDK9/cyclin T1 complex was reported previously to be required for the replication of other viruses of Herpesviridae origin, we next verified the antiviral effect of FIT-039 on tion through phosphorylation of the CTD of RNA polymerase II and viral proteins, such as the ICP22 of HSV. The ICP22-CDK9 complex was reported previously to phosphorylate the CTD of RNA polymerase II and regulate the transcription of HSV (20,22). A previous study showed that CDK9 was localized to nuclear viral transcriptosomes at the immediate-early stage of the HCMV infection, which allowed the active transcription of HCMV IEGs (14).…”
Section: Discussionmentioning
confidence: 94%
“…CDK1 was shown to activate the expression of HSV-1 late genes (19), while CDK2 promoted the replication of adenovirus, papillomavirus, and herpes virus DNAs (7). CDK7 and CDK9 were shown to activate viral RNA transcription in HIV and HSV (7,14,15,(20)(21)(22)(23)(24). Feichtinger et al recently described the interaction between CDK9/cyclin T1 and viral mRNA export factor pUL69 in human cytomegalovirus (HCMV), which belongs to the β subgroup of Herpesviridae (20).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][21][22][23][24][25][26][27][28][29][30][31][32][33][34] For instance, the Cdk9-interacting cellular factors comprise MyoD, retinoblastoma protein (pRb), p53, c-Myc, hSPT5 and gp130. 5 In these cases, the Cdk9-related pathway controls the phosphorylation of the aforementioned cellular factors.…”
Section: Resultsmentioning
confidence: 99%
“…It localizes in the nucleus of infected cells and functions as a transcriptional repressor for both viral and cellular genes (5). Furthermore, ICP22 associates with transcriptional complexes containing the viral transactivator protein ICP4, RNA polymerase II (4,9,14,16), and other host factors, including cdc25C (25,26) and cdk9 (7). Previous studies have reported that both UL3 and UL4 are expressed late in infection and are dispensable for viral replication in cultured cells in vitro (2,8,12).…”
mentioning
confidence: 99%